Ultrasonic Pulse Velocity – Strength Relationship for Concrete Subjected to Sulfate Attack (Iraqi Journal of Civil Engineering, 2012)
The purpose of this paper is to investigate the relationship between the Ultrasonic Pulse Velocity (UPV) and the compressive strength and the flexural strength of hardened concrete when subjected to different concentrations of sulfate attacks. The specimens used in the studies were made of concrete with different water-cement ratios (w/c). The UPV measurement and compressive and flexural strengths tests were carried out for concrete specimens of ages (4-40) days. The experimental results show that the relationship between UPV and the compressive and the flexural strengths of concrete is significantly influenced by age and the concentration of sulfate attack. The UPV and the compressive strength of concrete grow with age, but the growth rate varies with w/c ratio. It is found that with the same concentration of sulfate attack, a clear relationship curve can be drawn to describe the UPV and compressive and flexural strengths of hardened concrete. This paper presents the UPV-strength relationship curves for concrete having different (w/c) ratios subjected to different concentrations of sulfate attack. These curves are thought to be suitable for prediction of hardened concrete strength with a measured UPV value when sulfate attack is considered. It is concluded that the UPV increases with the increase of the compressive and flexural strength. The observed range for UPV was (3.5 to 4.75 km/sec) corresponds to (24 to 28.5 N/mm2) for compressive strength and to (4.6 to 6.5 N/mm2) for flexural strength. The UPV decreases with the increase of the concentration of sulfate exposure. The obtained maximum reduction in UPV was 31.6% with respect to the control spacemen at age of 40 days.